THE EXCELLENCE OF THE SPORT COACH. A CASE STUDY (Fiep Bulletin - online, 2010)
The aim of this study was to identify the values and the references that guide Professor Percy Oncken, a Brazilian volleyball coach and winner of various world-wide championships, in his work. The research technique used was "life stories". The data was collected by carrying out in-depth interviews and non-participative observation. Among the concerns that have followed his life-long career, we can highlight his great passion for his profession, respect for athletes and determination when facing difficulties. In terms of ambitions, we can point out the will to do his best every day and to one day train senior athletes. He regards difficulties that arise as being indispensable to a process of perfection. Having deprived his family of his attention is what has distressed him the most. The most important moments of his career were when he achieved good results and the ones that generate more suffering are those when he dismisses players from the national team. In terms of his social intervention, he is concerned with permanently carrying out his work with great quality and fully developing athletes.
Keywords: excellence; coach; life stories